Semantic Analysis of Landscape Terms in Uzbek and English Languages - Usmonova kizi (Penerbit Jurnal Indonesia, 2024)
The article analyzes the semantics of landscape terms in the Uzbek and English languages, their use in our speech, and the scientific research works of scientists. Also, the meaning of the word landscape and the introduction of this word into linguistics and the morphological features of terms with landscape archetypes in Uzbek and English languages ​​are highlighted.